2008
DOI: 10.1111/j.1547-5069.2008.00240.x
|View full text |Cite
|
Sign up to set email alerts
|

Creating a Healthy Workplace for New‐Generation Nurses

Abstract: Generation Y nurses in Quebec, faced with high levels of psychological distress because of their exposure to difficult nursing work environments, might leave the profession thereby exacerbating an already salient nursing shortage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
83
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 40 publications
6
83
1
3
Order By: Relevance
“…Difference in age was not significantly associated with personal experience of mental health problems, in either of the four groups. This contrasts with previous studies in which age differences in prevalence of mental health problems have been found, specifically higher prevalence of mental illness in younger nurses (Morrissy et al, 2013;Arafa et al, 2003;Christensson et al, 2011;Lavoie-Tremblay et al, 2008;Ryan and Quayle, 1999;Letvak et al, 2013).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Difference in age was not significantly associated with personal experience of mental health problems, in either of the four groups. This contrasts with previous studies in which age differences in prevalence of mental health problems have been found, specifically higher prevalence of mental illness in younger nurses (Morrissy et al, 2013;Arafa et al, 2003;Christensson et al, 2011;Lavoie-Tremblay et al, 2008;Ryan and Quayle, 1999;Letvak et al, 2013).…”
Section: Discussioncontrasting
confidence: 55%
“…Age difference in prevalence of mental health problems in nurses has been found in a number of previous studies Prevalence of mental ill health has been found to be high in studies of younger nurses (43.4% in LaVoie-Tremblay et al, 2008;Ryan and Quayle, 1999). Older nurses (over 60) have been found to have better mental health but higher prevalence of health problems per se than younger nurses (Letvak, Ruhm and Gupta, 2013).…”
Section: Age and Years Of Experiencementioning
confidence: 99%
“…Extrinsic effort in the nursing profession includes working under time pressure, interruptions, carrying responsibility, working overtime and physical demands. Extrinsic reward includes respect and support from superiors and (close) colleagues, job security, promotion opportunities, fair treatment and pay, and applicability of education and training on the job (Lavoie-Tremblay, Wright, Desforges, Marchionni, & Drevniok, 2008). The ERI model also has an "intrinsic imbalance" component, focusing on personal differences related to employees' job involvement and internally driven personal investments at work.…”
Section: Effort-reward Imbalancementioning
confidence: 99%
“…One prominent example would be 'work environments'. Studies grapple with issues such as the support, empowerment and opportunity they provide/do not provide (Haugh and Laschinger, 1996;Almost and Spence-Laschinger, 2002;Tourangeau et al, 2009), or their social functioning and what makes them psychologically healthy or unhealthy (Leveck and Jones, 1996;Dendaas, 2004Dendaas, , 2010Lavoie-Tremblay et al, 2008;Vessey et al, 2009), or how their architecture and design features can impact care and outcomes (Williams, 2001;Parker et al, 2004;Becker, 2007;Marquardt and Schmieg, 2009). Similarly, nursing environment has also emerged in discussions of leadership capacity, such as settings for practice enhancement and development strategies (McCormack and McCance, 2011;McCormack et al, 2013), as 'contexts' -with political, economic and social variability -that help or hinder research knowledge translation (Kitson et al, 1998;Rycroft-Malone, 2004;Rycroft-Malone et al, 2013) and in specific forms as high performing and attractive 'magnet' institutions (Scott et al, 1999;Buchan, 1999;Upenieks, 2003).…”
Section: The Second Wave: Environment As a Broad Empirical Concernmentioning
confidence: 99%